PERSONALITY AND INFORMATION PROCESSING: A COMPUTER-ASSISTED TECHNIQUE OF PREDICTING AGENT’S ACTIVITY AND EMOTIONAL STABILITY - Eleonora Nosenko; Iryna Arshava; Kostyantyn Kutovyy (European Scientific Journal, ESJ, 2014)
A computer-based information-processing technique, simulating the process of information exchange between the “virtual pilots” and “flight controllers”, patented by the authors as a “Method of predicting the individual’s stability to failure stress” (patent of Ukraine №91842, 2010) has been empirically proved to be predictive of the individual’s agentic activity as well. The conclusion was made on a sample of 60 participants, split into 2 clusters (K-means algorithm), by comparing their personality characteristics and the modes of information processing. One of the cluster’s participants demonstrated the abilities to simultaneously attend to the two different perceptual activities (identifying “call-names” and processing the visually perceived information) and equally high levels of efficacy of performance of both activities. The members of another cluster concentrated on one of the activities, partially ignoring the instruction to identify call-names, which is claimed to be a sign of susceptibility to stress. The clusters with different modes of information processing appeared to differ statistically significantly by t-test: on their psychological well-being measures, the strategies and attributions preferred and coping strategies. Between-cluster differences are significant: on the key strategies and attribution scales: success-expectation scale (t=8,87, p ≤ .001); the master-orientation scale (t=8,17, p ≤ .001), and task-irrelevant behavior scale (t= - 8,99, p ≤ .001); as well as on all the scales of psychological well-being and coping behavior. The results clearly suggest the conclusion about the validity of the technique for predicting both: the emotional stability and the agentic activity of the individual.